Failing to Learn English - Ritesh Karmaker (Indonesian Journal of Multidiciplinary Research, 2023)
This article serves as an excellent illustration of how the use of English in academic contexts is an essential part of learning the language. The students' struggle with learning English, however, is considerable. In Bangladesh, particularly Sherpur Sadar Upazilla, the existence, and use of English have a remarkable influence on students' techniques of communication and learning. The environment for learning has been improved by learning English practices. The article's writing process and the collection of data sources are qualitative. Students from Sherpur Sadar cannot study with Bangladeshi students due to the protocol. Students strive hard to keep up with the learning trend because there are many challenges to learning English, yet the majority of them fail. Students try to follow the learning trend despite several obstacles to English learning, yet the majority of them fall behind. Students strive hard to keep up with the trend because learning English is difficult, yet the majority of them fail. In Bangladesh, there are many barriers to learning English. Due to their academic difficulties, our students frequently overlook English. The result is that despite all the obstacles, they hardly ever learn English. Issues must be resolved because acquiring knowledge of English requires a setting that is conducive to learning the language.